Monetary Policy Under the Impact of the Current Global Crisis - Zina Marcu (CES Working Papers, 2013)
The issue of the financial crisis draws more and more the specialists' attention. The monetary policy has a decisive role in monitoring and reducing the inflationary phenomenon as much as possible, since it can become a real danger for an economy during a period of crisis. Inflation is a negative thing that affects the economy. It discourages the investments and the economic growth. The aim of this paper is to find the Central Bank's economic instruments and levers that can contribute to price stability in the economy. It was found that the elaboration of a measure of monetary policy with a restrictive feature can contribute to price stability on long term, but we should take into account the macroeconomic context in which it is applied.
Keywords: E31; E52; E58; G01; 330; central bank; inflation targeting; monetary policy; price stability Romania